Identifikasi Gaya Batang Tekan pada Baja Profil Siku untuk Berbagai Macam Tumpuan melalui Metode Vibrasi - , Purwandy Hasibuan, Prof. Ir. Hrc. Priyosulistyo, M.Sc.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Investigation of characteristics of structural elements using vibration method has been widely applied, especially in predicting internal forces of the elements by employing several theories that have been developed recently. In a truss structure, which comprises many elements of angled cross section, an eccentricity may take place due to the different position between centers of area of angled cross section and connection, that might violate the existing vibration theory. Slender element of single angled steel of L.30.30.3 of 120 cm in length with 10 variations of support type that are pined, clamped and partly clamped were tested under axial compressive load and applying the vibration method simultaneously. Stage of loading was carried out at load intervals of 1 kN at clamped-clamped and 0,5 kN for other type of support combinations. The natural frequency at each stage of load interval was evaluated by considering beam vibration theory of flexural, flexural-torsional and elastically constrained ends to get the characteristics of end rotational stiffness. The results showed that increasing the axial compressive load led to a reduction of the natural frequency of the structure. The theory of end rotational stiffness for pined (Ï=0) and clamped (Ï=â) are difficult to occur on the implementation. Analytical value of the axial compressive force by the data regression of the frequency for combinations of pined-pined, clamped-clamped and pined-clamped provide better accuracy than that the preliminary data of the frequency of the test results. The average relative error was indicated by 0,19%, 8,63% and 0,52% for pined-pined, clamped-clamped and pined-clamped respectively. Statistically, the analytical value provides the Coefficient of Variation (COA) of 0,2%, 10,2% and 1% for pined-pined, clamped-clamped and pined-clamped, which proves the uniformity and the significance of the two sets of the data.